Altar e Ambão: a presença de Cristo na palavra e na eucaristia, visível no espaço sagrado da comunidade - Delgado, Enrique Antonio Illarze (2013)
This academic work is a profound and diversified study on the Christian liturgical space, place of gathering of the community of faith with his Lord, Jesus Christ, the incarnated Logos, visible in the Word and in the Bread and Wine of the eucharistical meal, as expressed in the physical foci of the ambo and the altar/table. The consideration of the subject leads, firstly, to the research of the characteristics that the physical space of a theophany must have, entailed to the transcendentals of Beauty, Truth, Goodness and Harmony, meant by Plato as qualities of the divine essence. Attempt is made in order to understand how transcendentals were seen along history and also in the thought of Plotinus, Augustine, Kant and Hegel. Inmediately, in an multidisciplinarian way are introduced the contributions of a theology of aesthetics and sacraments in dialogue with Philosophy, Ethics, History, Architecture, Liturgy and Holy Scripture, with glimpses on the Anglican, Lutheran and Roman Catholic traditions. There are, also, an unfolding on how architects reflect and work around the concrete expressions of the divine immanence and transcendence in Architecture, trying to express the Unexpressable, and relating, in this way, the Fine Art of Architecture to Christian Faith. Following on the way, an accurate research is made on the ambo and the altar, physical foci of the divine Presence, viewing them from the point of view of theological typologies and their use in the three denominations afore said. Finally, and bearing in mind as theoretical base the philosophy of architecture and the philosophical hermeneutics of Gadamer, is made a critic of concrete liturgical spaces, designed and built by the architect Maria Ines Bolson Lunardini, specialized in sacred architecture and working in the city of Porto Alegre (RS) and its metropolitan area. In this manner, the theoretical study developed along this work dialogues with a concrete context. Thesis points out that ambo and altar/table are, in the context of the sacred space where the community of faith is summoned and gathers, the place of the living Presence of the Incarnated Logos.